Correlation between Mean Arterial Pressure Examination Values and the Incidence of Pre-eclampsia in Pregnant Women at Sultan Suriansyah Hospital, Banjarmasin - Harni, Putri; Ruslinawati; Masdiputri, Sri Nuriaty; Okvitasari, Yenny; Anisa, Noor (Fakultas Kedokteran, Universitas Papua, 2025)
Pre-eclampsia is one of the pregnancy complications that contributes to maternal and fetal morbidity and mortality. Early detection of this condition is crucial to prevent more severe complications. Mean Arterial Pressure (MAP) is one of the screening methods that can be used to assess the risk of pre-eclampsia in pregnant women. This study aimed to analyze the correlation between MAP examination values and the incidence of pre-eclampsia in pregnant women at Sultan Suriansyah Hospital, Banjarmasin. This research employed a correlational study design with a cross-sectional approach. The study sample consisted of 187 pregnant women selected through purposive sampling. Data were collected from medical records and observation sheets. Data analysis was performed using the Chi-Square statistical test. The results showed that among the 187 respondents, 131 pregnant women (70.1%) had MAP values >90 mmHg, categorized as being at risk of developing pre-eclampsia, and 56 pregnant women (29.9%) were diagnosed with pre-eclampsia. The statistical analysis revealed a significant correlation between MAP values and the incidence of pre-eclampsia (p-value = 0.000; p < 0.05). The study concludes that there is a significant correlation between MAP examination values and the incidence of pre-eclampsia in pregnant women at Sultan Suriansyah Hospital, Banjarmasin. Therefore, MAP can be utilized as a screening method for early detection of pre-eclampsia risk. Health workers are expected to enhance MAP monitoring in pregnant women to reduce the incidence of pre-eclampsia and its related complications.